Design and Implementation of a Web-Based Inventory and Sales Management System for Micro Retail Enterprises - Msyelga Fitriaaisyah; Irwansyah (Journal Innovation in Information and Computer Technology, 2025)
Micro retail enterprises often face challenges in managing inventory and sales due to their reliance on manual recording systems, which can lead to data inaccuracies, inefficiencies, and delays in decision-making. This study aims to design and implement a web-based inventory and sales management system to address these issues and improve operational performance. This research adopts a system development approach using the Waterfall model, which includes requirement analysis, system design, implementation, and testing. Data were collected through interviews and observations to understand the existing business processes and identify user needs. The system was developed as a web-based application that integrates inventory management and sales transactions into a single platform. The results show that the implemented system significantly improves data accuracy, reduces transaction processing time, and enables real-time report generation. The integration of inventory and sales functions helps minimize discrepancies and enhances overall efficiency in business operations. In conclusion, the proposed system provides a practical and effective solution for micro retail enterprises by offering a user-friendly, accessible, and scalable platform to manage inventory and sales activities.